(untitled) (Bangladesh Journal of Medical Science, 2024)
A rare autoimmune disease called anti-NMDAR encephalitis usually affects young people and frequently manifests as cognitive deterioration, seizures, and psychiatric symptoms. The diagnostic challenge and the importance in recognizing the clinical features and employing appropriate laboratory and imaging techniques for accurate and timely diagnosis will be discussed. We describe the example of an 8-year-old girl who suddenly began exhibiting strange behavioral and speech problems. Anti-NMDAR encephalitis was diagnosed after further investigation. This casee illustrates how different clinical presentations can lead to a delay in the disorder’s diagnosis. Healthcare practitioners continue to have difficulties in diagnosing heterogeneous clinical manifestations of anti- NMDAR encephalitis, particularly in the juvenile age range. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1233-1237